Plan de negocios para la creación de una empresa organizadora de eventos sociales en el Valle de los Chillos - Salas Herrera, Andrea Carolina (2019)
The present project presents a business plan for the creation of a company that organizes social events in Valle de Los Chillos, which has been distributed in different chapters that have contributed to the research. It begins with a literature review, in which the origin of social events throughout history is mentioned, the conformation of this type of companies and the application they have had in the city of Quito. For the market analysis, a descriptive research with a mixed approach is used, that is, quantitative, applying 60 surveys to the target and qualitative market with interviews to industry experts in order to measure the acceptance of the business and the needs of the companies to establish a specific client profile. As for the strategic plan, the macro and microenvironment that this business faces is analyzed, as well as the organizational culture of the company that is essential to have a clear objective about its nature. The key strategies that were established are the product development by establishing three event packages and the brand presence strategy that has some tools to be able to penetrate the market properly. In addition to this, flowcharts are created to be able to clearly establish the processes and see the functions that each collaborator performs. The blueprint is also a tool that helps to have clarity about the execution of the entire process of organizing events. Finally, a financial plan is made where indices were established that reflected that the project is viable and profitable. Below you can detail more thoroughly all of the above.